Assessment of Syndemic Inter-relationships between Substance Use, Violence and HIV Risk Among Persons Seeking Emergency Care in Nairobi, Kenya - J. Austin Lee; Timmy Lin; Janette Baird; Beatrice Ngila; Janet Sugut; John Kinuthia; Harriet Waweru; Daniel K. Ojuka; Michael J. Mello; Adam R. Aluisio (Journal of Clinical Research In HIV AIDS And Prevention, 2026)
Introduction Contemporaneous substance abuse, violence and HIV/AIDS risks (SAVA) result in synergistic negative impacts (syndemic effects). Presence of and risks for syndemic SAVA conditions are common among emergency department (ED) patients, however research on these inter-related processes is limited in sub-Saharan Africa. This study utilizes structural equation modeling to examine the relationships of syndemic SAVA conditions among persons seeking emergency injury care in Nairobi, Kenya. Methods This secondary analysis of a prospective observational study examined SAVA syndemic conditions among non-pregnant, adult ED injury patients able to provide consent at Kenyatta National Hospital. Structural equation modeling using diagonally weighted least squares (DWLS), was used to quantify associations between three latent variables (substance use, HIV risks, violence exposure). HIV risk included partner HIV status, men who have sex with men (MSM), and gay identities; violence exposure covered emotional, physical or sexual violence in the past six months; substance use encompassed positive screening for alcohol use disorder, poly-substance use, injection drug use and injury-related substance use. Model fitness was assessed using the Bentler-Bonett Normalized Fit Index (BB NFI), Goodness of Fit Index (GFI) (>0.9) and standardized root mean square residual (SRMSR) (< 0.05). Covariance between the latent factors was estimated. Results Among 2,368 screened ED patients, 665 were enrolled. Males were 83% of the sample; median age was 30 years (IQR: 24-38). Fit indices using DWLS showed a close fitting model (GFI=0.99, BB NFI=0.95, SRMSR=0.04). The indicator variables had significant loadings on two of the three syndemic factors (substance use and violence exposure, β range 0.10-0.95); in the SEM only MSM status had a significant loading on HIV risk, which was insufficient to confirm the identification of the latent factor. Violence exposure and substance use risk had significant positive covariance (0.30, p<0.001). Discussion and Conclusion This study provides the first available data from ED patients in sub-Saharan Africa on SAVA conditions, showing a co-relationship of violence exposure and substance use but no significant associations with HIV risk. These results can be used to inform programmatic interventions for higher-risk persons addressing synergistic conditions during emergency care.
Keywords: Emergency medicine